(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Preterm labour & delivery are very challenging obstetric complications encountered by obstetricians. In this study we tried, to determine the incidence, risk factor and pregnancy outcome of patients presenting with preterm labour in Combined Military Hospital. Its a retrospective study in the department of Gynecology & Obstetric, Combined Military Hospital, Chittagong Cantonment from July 2012 to June 2013. Sample size: 116. Inclusion Criteria: Gravid women both primi and multi. Pregnancy of more than 28 weeks duration but less than 37 completed weeks of gestation. Patient is in active labour. Exclusion Criteria: Labour pain started before 28 weeks of pregnancy. Induced preterm labour in any cases like PIH, eclampsia, Preeclampsia, APH, foetal IUGR, etc. Incidence of preterm labour was 22.30% in this study. Preterm rupture of membranes and infection were the commonest causes of preterm labour. Significant risk factor associated with preterm labours in this study are maternal age <20->35 years, low socio-economic condition, lack of proper antenatal care, multiple pregnancy etc. Irrespective of use of a course of steroid neonated mortality was significantly high in babies before 34 weeks. Other perinatal outcomes of preterm labour are birth asphyxia, RDS, neonatal jaundice and septicemia. High incidence of preterm labour being the most serious problem facing our obstetrician. The incidence is higher in our set up, compared to the developed countries. As prevention is naturally best way to combat preterm labour, some modifiable risk factors are identified. Health care provider may encounter maternal age, nutritional status, infection and can identify the target population for betters prenatal care. JCMCTA 2014 ; 25 (2) : 41-45